2017
DOI: 10.1021/acs.jpcb.6b12408
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Intramolecular Proton Transfer of Alizarin Investigated by Femtosecond Stimulated Raman Spectroscopy

Abstract: We report time-resolved stimulated Raman spectra of alizarin in DMSO solution with 403 nm excitation. Upon photoexcitation, the intramolecular proton transfer reaction of alizarin occurs in 70-80 fs, which is confirmed by both the population growth and the frequency and bandwidth changes of skeletal vibrational modes of alizarin. Interestingly, the vibrational frequencies of ν(C═C) and ν(C═O) show opposite shifts during the reaction, which may implicate changes in the resonance structure of anthraquinone and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 62 publications
8
60
1
Order By: Relevance
“…A home-built FSRS setup based on a 1 kHz Ti:sapphire regenerative amplifier has been used for time-resolved Raman measurements [43,44]. The broadband Raman probe was generated by supercontinuum generation in an yttrium aluminum garnet crystal (4 mm thick, Newlight Photonics, Toronto, ON, Canada) and filtered by a long pass filter (830 DCLP, Omega Optical).…”
Section: Femtosecond Stimulated Raman Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…A home-built FSRS setup based on a 1 kHz Ti:sapphire regenerative amplifier has been used for time-resolved Raman measurements [43,44]. The broadband Raman probe was generated by supercontinuum generation in an yttrium aluminum garnet crystal (4 mm thick, Newlight Photonics, Toronto, ON, Canada) and filtered by a long pass filter (830 DCLP, Omega Optical).…”
Section: Femtosecond Stimulated Raman Setupmentioning
confidence: 99%
“…Since Mathies and co-workers first introduced the femtosecond stimulated Raman spectroscopy (FSRS) to the ultrafast dynamics and transient Raman measurements of all-trans-β-carotene in the S 2 and S 1 excited states [39,40], FSRS with both high spectral (<10 cm −1 ) and temporal (<50 fs) resolutions has been widely applied to many excited state processes including the intra-and inter-molecular proton transfers [41][42][43][44], charge transfers [45][46][47][48], electron transfers [49][50][51][52]. A broadband Raman probe pulses combined with a narrowband Raman pump were used for FSRS, and the transient Raman bands of the ground and excited electronic states can be obtained at the same time in a wide frequency range covering most of the fingerprint region (800-2200 cm −1 ) [43,53]. Recently, McCamant and co-workers reported the FSRS measurements on 4-(dimethylamino)benzonitrile (DMABN), where the ultrafast ICT dynamics with the twist of the DMA group was clearly shown [46].…”
Section: Introductionmentioning
confidence: 99%
“…Based on DFT//TDDFT/B3LYP/6‐31G(d) level in toluene solvent, we construct the PESs for the Ia system in both S 0 and S 1 states with fixing both O1―H2 and O4―H5 bond lengths. Herein, we want to mention that although previous work has reported that the TDDFT theoretical level might not provide the sufficiently accurate ordering of closely spaced excited states, theoretical results have shown the reliability of this method to offer qualitative energetic pathways for ESIPT behaviors . Specifically, the constructed PESs of both S 0 and S 1 states are through fixing O1―H2 and O4―H5 ranged from 0.9 to 2.1 Å in step of 0.1 Å (see Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we want to mention that although previous work has reported that the TDDFT theoretical level might not provide the sufficiently accurate ordering of closely spaced excited states, theoretical results have shown the reliability of this method to offer qualitative energetic pathways for ESIPT behaviors. [56][57][58][59][60][61][62][63][64] Specifically, the constructed PESs of both S 0 and S 1 states are through fixing O1-H2 and O4-H5 ranged from 0.9 to 2.1 Å in step of 0.1 Å (see Figure 4). As shown in Figure 4A, it could be clearly seen that the potential energy increases along with the elongation of O1-H2 and O4-H5 bond lengths.…”
Section: Resultsmentioning
confidence: 99%
“…This qualitative result was later supported by the nodal plane model by Nagaoka and Nagashima ( 18 ). More recent transient spectroscopic work has measured the rate of ESIPT ( 19 21 ) as a femtosecond process and correlated this with pigment fading ( 11 , 22 ). However, these are all condensed phase experiments where the effects of secondary molecules, such as solvent molecules or other pigment components, cannot be completely excluded, which is particularly important since intermolecular effects are widely known to affect relaxation ( 20 , 23 ).…”
Section: Introductionmentioning
confidence: 99%